SILEGION (Sistem Informasi Legalisir Ijazah Online) At Universitas Pembangunan Nasional “Veteran” East Java - Faisal Muttaqin; Fawwaz Ali Akbar; Retno Mumpuni (Nusantara Science and Technology Proceedings)
The role of higher education to students is not only during the active lectures, but when the students have graduated, one example of the role of higher education that is still needed by students is when they want to do diploma and transcript legalization activities. Using information technology enables humans to obtain information from distant places in a short time and at a low cost. The process of legalizing diplomas at University of Pembangunan Nasional “Veteran” Jawa Timur has so far been carried out with a manual process that is if there are alumni who wish to legalize diplomas or transcripts, the alumni must come directly to their faculties or the legalization section by bringing their original diplomas and transcripts. The purpose of this research is how to create an information system that can help alumni to legalize the diploma process online. The method used in completing this research is by observation in the field, interviews and distributing questionnaires. By developing and implementing the SILEGION (sistem informasi legalisir ijazah online) application, it can make it easier for alumni to legalize online, especially those outside the city or outside the island. From the results of testing the average level of usability using four criteria, namely ease of use, ease of learning, usefulness and satisfaction on SILEGION information systems get a value of 80%. It states that the SILEGION (sistem informasi legalisir ijazah online) system that was built has a good level of usability